Women's Voices of the Caribbean Diaspora and the Creation of a Thirdspace in Josefina Báez's Performative Text - Martina Bařinová (Gender a Výzkum)
This study focuses on how the Caribbean diaspora is reflected in the novel Levente no. Yolayorkdominicanyork by the New York-based Dominican artist Josefina Báez. Through dialogues and anecdotes the author depicts the everyday life of a community of women living in an apartment building located in a Hispanic neighbourhood in New York. In a close reading, I read the apartment building, called 'Ni é', as a metaphor of a glocal community. The novel can thus be read through the lens of the postcolonial debate about centre and periphery. I also analyse the work through the lens of the thirdspace theory, which is an especially important concept for some feminist critics of gentrification of the social space, such as Gloria Anzaldúa and Barbara Hooper. My analysis of specific scenes from life on the periphery that the Ni é building and its inhabitants embody draws mainly on the theoretical work La subversión feminista de la economía by the Spanish feminist theorist Amaia Pérez Orozco. Orozco's critique of capitalist economy and her philosophy of microeconomics is compared with Josefina Báez's representation of the notion of home.